Selection of Rhizobium strain from Wonogiri, Central Java on the growth of soybean (Glycine max L.) on the sand sterile medium in greenhouse - SRI PURWANINGSIH (Biodiversitas Journal of Biological Diversity, 2005)
An experiment on the selection of Rhizobium strain from Wonogiri, Central Java on the growth of soybean (Glycine max L.) on the sand sterile medium in green house. The aim of the experiment the selection and potency of the Rhizobium strain to increase the growth of soybean. The experiment was carried out in green house condition in Microbiology Division, Research Center for Biology-LIPI with sterile sand medium. The research design was Completely Randomized Design with three replications for each treatment. The Rhizobium strains used were 1 W (isolated from bean, Vigna radiata), 2 W (isolated from soybean), 3 W (isolated from bean), 4 W (isolated from soybean), 5 W (isolated from soybean), 6 W (isolated from peanut, Arachis hypogaea), 7 W (isolated from peanut), 8 W (isolated from peanut), the controls were uninoculated with Rhizobium strain and without urea fertilizer (K1), uninoculated and with urea fertilizer equal 100 kg/ha (K2). The plants were harvested after 50 days, the variable of investigation were the dry weight of canopy, roots, nodules root, total plants, number of nodules and â€˜symbiotic capacityâ€. The results showed that all of experiment plant which be inoculated with Rhizobium able toform nodule. Strain of 2 W (isolated from soybean) has given the best effects on the growth of soybean.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: Rhizobium strain, Glycine max L, sand sterile